Air cured sisal strand reinforce cement sheet. (1st January 2002) - Blicblau, A.S.; Laird, S.; Coutts, R.S.P.
The aim of this project was to investigate the properties of natural fibre reinforced (Sisal) cement sheeting. Sisal strands were chemically treated and incorporated into cement to produce sheeting suitable for housing. Results from mechanical strength tests indicated Sisal reinforced cement was suitable for construction of dwelling walls or roofs.